Histological techniques for preservation of alginate bead structural integrity using glycolmethacrylate. (September 2013) - McGowan, Brittany H; Nagatomi, Jiro
Abstract : The applications of alginate as a drug delivery vehicle and 3D cell culture scaffold have become increasingly popular in the fields of biomaterials and tissue engineering. Although histological analysis of intact alginate scaffold and cells is a critical aspect of investigations, the existing methods of histological processing often lead to distortions in the scaffold shape, resulting in poor image quality and misrepresentation of the cellular environment. For this reason, the use of glycol methacrylate (GMA) has been explored as an embedding material of alginate scaffolds for histological analysis of embedded cells. The results of the present study demonstrated that soaking alginate scaffolds in a barium chloride solution prior to fixation in neutral buffered formalin (NBF) was a critical step for maintenance of the structure. By slowly infiltrating the hydrogel matrix with GMA using a commercially available embedding kit, the techniques developed in the present study allowed preservation of alginate bead structural integrity and successful staining of the embedded cells.